EDUCATIVE CARE PRACTICE WITH THE COMMUNITARIAN HEALTH AGENT IN A TRANSCULTURAL PERSPECTIVE - Giselda Hahn; Ana Lúcia C. Kirchhof (Universidade Federal do Paraná, 1999)
The Program of Health Communitarian Agents (PACS) is an emerging subject for nursing. Its discussion is necessary once the Health Communitarian Agents (ACS) training was delegated to the nurse. This study accounts the activities developed during the practice of social work of the MA of nursing at the UFSC (Federal University of Santa Catarina). It was developed with a group of seven ACS at Lajeado, RS. The aimvas to know the beliefs and values of the ACS in regarding health, as well as the relation of these beliefs and values to the knowledge they obtained in their training. Thus we will know the difficulties faced by them to perform the directions received from the nurse by attending the activities carried out by them in home visits, group works, and training meetings. So this study has been grounded on Madeleine Leininger's presuppositions of cultural universality and diversity in the care, and on Paulo Freire's proposal of a transforming popular education. In this way the study has shown the necessity for the nurse to be conscious of the role s/he has in the PACS. The ACS, on their turn, perform the activities they have been meant to with some difficulties. However, they help the nurse and other members of the health team as they evince the health demand in the community.